2014
DOI: 10.1371/journal.pone.0110435
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Respiratory Tract Infections in Children at the Pediatric Hospital in Ouagadougou (Burkina Faso)

Abstract: BackgroundAcute respiratory infections (ARIs) are a major cause of morbidity and mortality in children in Africa. The circulation of viruses classically implicated in ARIs is poorly known in Burkina Faso. The aim of this study was to identify the respiratory viruses present in children admitted to or consulting at the pediatric hospital in Ouagadougou.MethodsFrom July 2010 to July 2011, we tested nasal aspirates of 209 children with upper or lower respiratory infection for main respiratory viruses (respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
9
37
1
Order By: Relevance
“…Among the cases in which HPIV and HCoV were detected, HPIV type 3 and HCoV type OC43 were the predominant types, and this is consistent with previous studies . In this study, INFs were detected in 8.5% of the cases, which is in agreement with findings from the national influenza surveillance and other related studies in Africa among patients hospitalized with SARI . A higher influenza positivity proportion has been reported among outpatients with influenza‐like illness …”
Section: Discussionsupporting
confidence: 92%
“…Among the cases in which HPIV and HCoV were detected, HPIV type 3 and HCoV type OC43 were the predominant types, and this is consistent with previous studies . In this study, INFs were detected in 8.5% of the cases, which is in agreement with findings from the national influenza surveillance and other related studies in Africa among patients hospitalized with SARI . A higher influenza positivity proportion has been reported among outpatients with influenza‐like illness …”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, a study conducted by Koul et al has shown that influenza and rhinovirus were most commonly detected in respiratory samples [15]. However, RSV has been considered as a main etiologic agent of upper respiratory tract infection and pneumonia in children [16] even though rhinoviruses were most frequently detected. In our study, CoV-OC43, CoV-229E, MPV A-B, bocavirus, enterovirus, and parainfluenza virus 1 and 3 coinfections were found in children infected with influenza, which is underreported in Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…Influenza vaccination is not yet implemented in Burkina Faso and will require a proper understanding of the seasonal circulation of influenza viruses that has not reached a consensus yet. Previous surveillance studies during the early implementation of the influenza network in the country reported one peak of increased transmission but varying in timing (December 2010‐February 2011 and August‐October 2011) . A meta‐analysis using three different statistical approaches on three non‐comparable FluNet datasets (2011‐2013, 2010‐2014, and 2013‐2014) was not conclusive on the number or on the synchronicity of periods with increased influenza transmission .…”
Section: Discussionmentioning
confidence: 82%